Aнализ криминогенных и психологических причинных факторов, влияющих на формирование преступного поведения несовершеннолетних - Любимова, Дарья; Захария, Вирджиния (Tipografia „Adrilang”, 2022)
In recent years, the countries of the world community have been making a lot of efforts to form an effective system for the protection of the rights and prevention of juvenile delinquency. Nevertheless, many problems remain unresolved in this area, such as family problems, the prevalence of alcoholism, drug addiction and neglect, gaps in current legislation, as well as insufficient use of effective forms and methods of international cooperation. The prevention of juvenile delinquency and the development of appropriate recommendations are among the basic tasks of international law-making, as well as the formation of humane standards for the treatment of juvenile offenders, designed to ensure a rational youth and criminal policy. Measures to prevent offenses should be aimed at all children and adolescents without exception. In order to prevent the delinquent behavior of children, close cooperation with state and local government bodies and public associations is recommended.

В последние годы страны мирового сообщества прикладывают немало усилий по формированию эффективной системы защиты прав и профилактики правонарушений несовершеннолетних. Тем не менее, в этой сфере остаются неурегулированными многие проблемы, такие как неблагополучие в семье, распространённость алкоголизма, наркомании и безнадзорности, пробелы в действующем законодательстве, а также недостаточное применение действенных форм и методов международного сотрудничества. Предупреждение преступности и борьба с ней являются внутренним делом каждого государства, которое само определяет, в каких договорах следует участвовать, к деятельности каких международных организаций присоединиться и в каком объеме.
Keywords: criminogenic factors; juvenile delinquency; Republic of Moldova; cooperation; behavior; struggle; family trouble; social environment